Analysis of collapse resistance of offshore rigid frame - Continuous girder bridge based on time-varying fragility. (January 2021) - Liang, Yan; Yan, Jia Lei; Qian, Wei Xin; Cheng, Zhan Qi; Chen, Huai
Abstract: In service period, the key to ensure the service performance of bridge is to control its material durability damage and continuous collapse better. Nowadays, most anti - collapse analysis under earthquake is for the frame structure, the theory and method of anti - collapse analysis of bridge is not systematically summarized. Taking a 4 - span rigid frame - continuous girder bridge in offshore seismic prone region as an example, a new quantitative criterion for collapse resistance was proposed based on theoretical fragility, reliability theory and concept removal method of components, which is suitable for the example bridge. The results show that the time-varying durability damage and time-varying bond - slip effect on mechanical properties of materials can't be ignored in service period; the fragility and importance coefficient increase with service life, while the robustness coefficient decreases with service life, the different optimization algorithms all improve their corresponding parameters; when the bridge reaches its designed service life, its robustness coefficient is about 25% of that of the new, when the bridge exceeds the designed service life, its robustness coefficient decay rate is low, and the residual robustness coefficient is about 18%, the bridge still has certain anti - collapse performance. Highlights: Time-varying bond-slip effect is obtained by durability damage of material. The fragility, importance and robustness coefficient of bridge are presented. Exceeding probability of system is greater than that of component in service period. Time-varying collapse resistance analysis of bridge in service period is analyzed.